The Influence of Public Sector Accounting Systems and Budget Transparency on Quality Financial Reports in Local Governments - Suryanto, Suryanto; Kurniati, Poni Sukaesih (Labkat Press KA FTIK UNIKOM, 2025)
The caliber of local government financial reports serves as a crucial metric for evaluating the degree of accountability and openness in public financial management. Nonetheless, numerous local governments in Indonesia continue to face challenges in producing reliable financial reports that comply with accounting standards. This study aims to investigate the impact of public accounting systems and budget transparency on the quality of local government financial reporting. This study uses a quantitative approach with multiple linear regression analysis techniques. The study population encompasses all local governments in Indonesia, comprising 34 provinces, 416 regencies, and 98 cities. All populations are surveyed using the census method. Data were obtained from the 2023 BPK Audit Report, municipal budget records, and details regarding implementing SAP-based accounting systems. The research findings show that the public sector accounting system and budget transparency, both partially and simultaneously, have a positive impact on high-quality financial reporting. The determination coefficient (R2) of 0.682 shows that this component contributes 68.2% of the differences in high-quality local government financial reports. This study reveals that the integration between the implementation of the public sector accounting system and budget transparency plays an important role in realizing high-quality financial reporting. These findings are expected to be the basis for strengthening the regional financial governance reform agenda based on empirical evidence.